Family Planning 2020 and Nepal’s Pledge - Amatya, Archana; Dangal, Ganesh (Journal of Nepal Health Research Council, 2017)
Family planning 2020 is a global partnership which has been started after the 2012 London meeting on Family planning (FP) with the aim of improving the FP services to women and girls in the poorest countries. Achieving the FP2020 goal is critical to ensuring universal access to sexual and reproductive health and rights by 2030 as part of Sustainable Development Goals.